An Experimental Study Based on the Strength Properties of Concrete Containing Chemical Admixture - Tugrul, Esra (My University, 2019)
Today, the use of chemical admixtures has become widespread in the concrete sector. It is possible to further improve the performanceof concrete with the use of chemical admixtures. As the chemical admixture ratio increases, the concrete strength does not alwaysincrease. It is necessary to pay attention to the optimum contents recommended by the manufacturers for different types of admixtures.As well as the positive effect of chemical admixtures on concrete durability, it also provides benefits in workability and compaction. Italso has the advantages of reducing the concrete permeability and increasing the freeze-thaw stability. In this study, a high waterreducing superplasticizer as chemical admixture was used in concrete production. This is because; this admixture has the increasing theslump and spreading of concrete at a high ratio without changing the concrete consistency. In this study, a series of concrete specimenswere prepared by using the chemical admixture at a certain ratio. These specimens were conducted to concrete compressive and splittingtensile strength tests. In order to determine the effect of the chemical admixture on the concrete strength, a series of reference specimenswithout admixtures were prepared. Thus, the strength of concrete specimens with admixture and non-admixture were compared anddiscussed. As a result, it has been determined that the strength of the concrete is improved by the use of chemical admixture at a certainratio and type of admixture to produce the concrete with the desired properties.
Keywords: İnşaat Mühendisliği; İnşaat ve Yapı Teknolojisi